2019
DOI: 10.2134/jeq2019.02.0085
|View full text |Cite
|
Sign up to set email alerts
|

Direct Exports of Phosphorus from Fertilizers Applied to Grazed Pastures

Abstract: Since its discovery in 1669, phosphorus (P) in the form of fertilizer has become an essential input for many agroecosystems. By introducing a concentrated P source, fertilizers increase short‐term P export potential soon after their application and longer‐term export potential by increasing soil fertility (legacy P). The 4R concept was developed to help mitigate P exports from the fertilizers that sustain agricultural productivity. This review investigates the factors affecting P exports soon after the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 176 publications
(200 reference statements)
0
16
0
Order By: Relevance
“…For example, Owens et al (1994) reported groundwater NO 3 -N concentrations beyond USEPA potable water standards in watersheds connected to fertilized monoculture grass pastures that were grazed by beef cattle, compared to similar pastures where inter-seeded alfalfa was utilized to enhance soil fertility. These differences in nutrient concentration in drainage water also vary with the timing of nutrient applications and stocking rates (Julian et al 2017, Nash et al 2019. Julian et al (2017) reported a significant reduction in nutrient loading in catchment areas, after reducing the number of dairy cattle and sheep in grazing pastures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Owens et al (1994) reported groundwater NO 3 -N concentrations beyond USEPA potable water standards in watersheds connected to fertilized monoculture grass pastures that were grazed by beef cattle, compared to similar pastures where inter-seeded alfalfa was utilized to enhance soil fertility. These differences in nutrient concentration in drainage water also vary with the timing of nutrient applications and stocking rates (Julian et al 2017, Nash et al 2019. Julian et al (2017) reported a significant reduction in nutrient loading in catchment areas, after reducing the number of dairy cattle and sheep in grazing pastures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is important to understand that 10-80% of P losses can come from other parts of the farm such as recent fertilizer or manure (and dung) applications or unutilized forage (McDowell et al, 2007). Strategies are also available to reduce losses from these sources such as the application of sparingly soluble P fertilizers (Nash et al, 2019) or avoiding the grazing of wet areas that are well-connected to nearby streams . Each strategy varies in its cost and effectiveness and while costeffectiveness can be improved by targeting strategies to the sources of P loss, this may not be sufficient to enable WEP losses to meet the target nor do so without significantly reducing farm profitability (McDowell and Nash, 2012).…”
Section: Meeting Environmental Targetsmentioning
confidence: 99%
“…Ippolito et al (2019) show how irrigation type influences soil P dynamics, noting a difference in soil P availability between sprinkler and furrow irrigation, with greater Olsen‐extractable P in long‐term furrow irrigation. In Australasian settings, Nash et al (2019) detail the implications of varying hydrology on direct exports of P from fertilizer applications. They also describe how the use of information on local hydrology can help farmers identify principles for selecting fertilizers, to minimize risk of P loss, soon after application.…”
Section: Focusing On Place‐based Solutions: Think Globally Act Locallymentioning
confidence: 99%